Evaluating the impact of therapeutic handling on sit-to-stand movements post-stroke: Kinematic smoothness as a monitoring metric for recovery. - Yamasaki, Hiroshi R.; An, Qi; Takahashi, Koji; Fujii, Takanori; Yang, Ningjia; Itkonen, Matti; Yokoyama, Moeka; Alnajjar, Fady S.K.; Otomune, Hironori; Hattori, Noriaki; Miyai, Ichiro; Shimoda, Shingo (Journal of Bodywork & Movement Therapies, 2025)
Therapeutic handling during sit-to-stand (STS) tasks in post-stroke subjects targets complex motor pattern modifications, however, its impact on movement smoothness and the subject-specific responses remains underexplored. This study aimed to examine the effects of therapeutic handling on the movement smoothness during STS in post-stroke subjects, identifying recovery subtypes based on immediate changes in smoothness metrics and longitudinal motor functional improvements. Thirty-eight inpatient post-stroke subjects and five healthy controls participated in standardized STS, with and without therapeutic handling. Joint kinematics were recorded using a 3D mocap system, and the spectral arc length measure (SPARC) of joint angular velocity was analyzed to assess trajectory quality. Fifteen patients were re-measured after one month. Therapeutic handling significantly altered movement smoothness (direct effect). Trajectory smoothness after therapeutic handling (after-effect) was significantly correlated with the direct effect (r = 0.85, p < 0.01). The SPARC Delta, discrepancy between the direct and after-effect, negatively contributed to the improvement in FMA over time (p = 0.02). This emphasizes the importance of investigating subtypes of recovery based on the variability of smoothness response to therapeutic handling.